Future policy implications of tidal energy array interactions. (October 2019) - Waldman, S.; Weir, S.; O'Hara Murray, R.B.; Woolf, D.K.; Kerr, S.
Abstract: Tidal stream energy technology has progressed to a point where commercial exploitation of this sustainable resource is practical, but tidal physics dictates interactions between tidal farms that raise political, legal and managerial challenges that are yet to be met. Fully optimising the design of a turbine array requires its developer to know about other farms that will be built nearby in the future. Consequently future developments, even those in adjacent channels, have the potential to impact on project efficiency. Here we review the relevant physics, consider the implications for marine policy, and discuss potential solutions. Possible management paths range from minimal regulation to prioritise a free market, to strongly interventionist approaches that prioritise efficient resource use. An attractive exemplar of the latter is unitization, an approach to resource allocation widely used in the oil and gas industry. We argue that an interventionist approach is necessary if the greatest possible energy yield is to be produced for a given level of environmental impact. Highlights: Large tidal energy farms have potential to affect each other's energy output and revenue. Optimising energy extraction and income requires consideration of future developments. Existing planning and policy frameworks do not consider tidal farm interactions. Large scale use of tidal energy will benefit from strategic regional planning. For optimal use of the tidal resource, an interventionist approach is recommended.